F(x)=2x-1
g(x)=2x+4
Find (f+g)(x)
1 answer:
Answer:
(f+g)(x)=4x+3
Step-by-step explanation:
Given the functions f and g defined above, their sum f+g is defined by (f+g)(x)=f(x)+g(x). Using algebra, we thus have (f+g)(x)=2x-1+2x+4=4x+3.
You might be interested in
Answer:
This is a rip off but...
Step-by-step explanation:
The ocuse triangle is
- Rational
-Irrational
-Rational
-Rational
Just took the test
If the diameter is 10 the radius is 5 and the formula for area of a circle pie r squared so it be
Answer:
2/3
Step-by-step explanation:
5/6 - (1/8÷3/4)
=5/6 - (1/8 × 4/3)
=5/6 - ( 1/6)
=4/6
=2/3
Answer:
slope : 3/2 Y-intercept : 3 ------------> (0,3) (2,6) are the points
Step-by-step explanation:
<u>X | Y</u>
0 | 3
2 | 6